AN ANALYSIS OF CAUSALITY AND COINTEGRATION AMONG NIFTY BANK INDEX, PUBLIC AND PRIVATE SECTOR BANKS SHARE PRICES OF INDIA. - Dr. Santoshkumar; Kumar Sharma, Dr. Lalit; Kumar, Dr. Rajender (The journal of contemporary issues in business and government, 2022)
The current paper examines the long run and short run relationship between the bank nifty and other public and private sector banks listed on NSE. market and banking sector. Bank nifty is a major index on NSE. The data was collected from the official website of National Stock Exchange and invtesing.com. The nature of data used for the purpose is secondary. An empirical analysis using everyday data is conducted for 730 days, starting from 2nd January 2017 to 31st December 2019. Descriptive statistics, Unit root Test, Johansen Cointegration test, Granger Causality Test, Cointegration analysis and Impulse Response function are applied as major methodologies for analysis. Augmented Dickey Fuller Tests is applied to examine stationarity of all the variables, it was found that all the variable series were non stationary. JohnsenCointegration analysis shows that there is no long-term relationship among the variables. Granger Causality /Block Exogeneity test is used to identify the short run relationship and found RET BANK NIFTY, RET HDFC, RET KOTAK and RET ICICI have short run relationship. Impulse response function was also used to check the impact of one shock on another variables.